New IEC Standards Requirements to the Parameters of Powerful Electromagnetic Pulsed Disturbances - Kravchenko, V.I.; Knyazyev, V.V.; Koliushko, G.M.; Vavriv, L.V. (Радиофизика и радиоастрономия, 2002)
The European Union Directive on EMC defines a new concept of providing electromagnetic compatibility. The Directive mandates that all electromagnetic phenomena which can influence the operation of technical devices need to be considered. Electromagnetic phenomena which accompany high-altitude nuclear explosions are now on the list of standardized powerful electromagnetic pulsed disturbances which previously included only lightning and electrostatic discharges. The purpose of this paper is to familiarize the developers of the electronic, radio electronic and electrical products with the new EMC requirements set to those products. Директива Европейского Совета по EMC определяет новую концепцию обеспечения электромагнитной совместимости. Директива предписывает рассматривать все электромагнитные явления, которые влияют на работу технических устройств. Электромагнитные явления, которые сопровождают ядерные взрывы на большой высоте, включены в перечень стандартных мощных электромагнитных импульсных возмущений, который ранее включал в себя только молниевые и электростатические разряды. Целью настоящей работы является ознакомление разработчиков электронной, радиоэлектронной техники и электрических устройств с новыми требованиями к электромагнитной совместимости. Директива Європейської Ради з EMC визначає нову концепцію забезпечення електромагнітної сумісності. Директива наказує розглядати усі електромагнітні явища, що впливають на роботу технічних пристроїв. Електромагнітні явища, що супроводжують ядерні вибухи на великій висоті, включені до переліку стандартних потужних електромагнітних імпульсних збурень, до якого раніше входили тільки блискавкові та електростатичні розряди. Метою цієї роботи є ознайомлення розробників електронної, радіоелектронної техніки та електричних приладів з новими вимогами до електромагнітної сумісності.